Fetal Development of the Orbit - Gaca, Piotr Jakub; Lewandowicz, Michael; Lipczynska-Lewandowska, Malgorzata; Simon, Michael; Matos, Philomena A. Wawer; Doulis, Alexandros; Rokohl, Alexander C.; Heindl, Ludwig M. (Klinische Monatsblätter für Augenheilkunde, 2022)
Human prenatal development is divided into an embryonic period and a fetal period. Intense organogenetic activity occurs in the embryonic period of prenatal life, while the fetal period is marked by less intense changes. Knowledge of the embryology of the orbit not only allows insights into how normal variations in the orbital structure arise but also provides an understanding of how congenital deformities occur when normal orbital development goes awry. In order to explore our understanding of the developmental anatomy of the orbit during the fetal period of prenatal life, the authors have summarized the major milestones in orbital morphogenesis, a temporally precise and morphogenetically intricate process. This process can be considered as an anatomic series of complex, well-orchestrated changes in morphology as well as a series of complex biochemical and molecular events that coordinate and control the anatomic development. Identifying and linking signaling pathways and regulatory genes linked with normal orbital morphogenesis is a crucial step to offer patients with chronic or incurable orbital diseases effective treatment options in the future.
Keywords: embryology; orbitmorphogenesis; anatomical anomalies; milestones